Social Support and Psychological Well-being of GBKP Pastors: The Moderating Role of Job Satisfaction - Perianatalina Sitepu; Siti Aisyah; Nina Siti Salamiah Siregar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study analyzes the influence of social support on the psychological well-being of GBKP pastors, with job satisfaction as a moderating variable. Employing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis on questionnaire data collected from active GBKP pastors, the results indicate that social support has a positive and significant effect on psychological well-being (coefficient = 0.503, P-Values = 0.000). Job satisfaction also positively and significantly influences psychological well-being (coefficient = 0.265, P-Values = 0.000). Furthermore, job satisfaction significantly moderates the relationship between social support and psychological well-being (T-Statistics = 2.709, P-Values = 0.007). The research model explains 58.1% of the variance in pastors' psychological well-being (R-Square = 0.581), demonstrating good predictive relevance (Q-Square = 0.380). The implications of this study suggest that enhancing social support and job satisfaction is crucial for maintaining and improving the psychological well-being of pastors.